Experiências do chão da escola : uma convivência entre orientação ciência, tecnologia e sociedade e bom desempenho na Prova Brasil - Sousa, Carlos Erick Brito de (2019)
The Science, Technology and Society (STS) movement was initiated in the late 1960s, reflecting a new way of perceiving the social implications of science and technology. When inserted in the school context, this movement is intended to learn scientific content considering the technological, political, economic, ethical, historical and social aspects of science, aiming to develop critical thinking, problem solving ability and decision making. On the other hand, the school system's concern with the performance of large-scale exams is constant, leading to student training practices aimed at enhancement and improving performance. In view of this context, this doctoral thesis seeks to respond the following inquiry: How is it possible the coexistence and/or imbrication between pedagogical practices with traces of STS orientation and the preparation for the national large-scale exam, in a school with a good performance in this test? The two aspects, in principle, are not convergent, however, this study seeks to demonstrate the possibility of developing an educational proposal with traces of STS orientation concomitant to the preparation to obtain a good performance in a large-scale exam. In this sense, an investigation was developed in a school of the public system of Maranhão, with a good concept in the “Índice de Desenvolvimento da Educação Básica (Ideb)” (Development Index of Basic Education) and good performance in the “Prova Brasil” (Brazil Exam). This research aimed to analyze pedagogical practices with traces of STS orientation in a school with good performance in a large-scale exam, investigating possible relations between these two different perspectives. The present work is qualitative and is characterized as a case study, using different strategies and data collection tools, including daily school observations, questionnaires, interviews and analysis of school documents. Thus, interviews were conducted with nine teachers, a pedagogical coordinator, and questionnaires were applied with 40 students from the Middle School. All the stages of the field research were developed in the own school space. The data obtained were analyzed using interpretative analysis and content analysis procedures. It was adopted the ethical parameters required to researches of this type in Brazil. The results obtained attest to the investment in integrative teaching proposals, with collaboration between teachers of different disciplines, and in Project Pedagogy, with the implementation of works that value interdisciplinarity, bringing the family and the community closer to direct participation in the experiences of the school. The study of these pedagogical experiences allowed to diagnose educational practices with elements of STS orientation, and a coexistence of these initiatives with pedagogical actions destined to the preparation for the national exam, with some relations of imbrication between the two proposals, that strengthen the mutual development of the two perspectives in the school space. These findings make it possible to defend the thesis which a school that performs well on large-scale exams, although concentrating efforts on technical training, with pedagogical practices designed to prepare for proficiency, it can also make a space for the development of experiences that favor human and citizen formation. Therefore, although the two aspects studied by this research are in a tension zone, having different origins and operational logic, this work demonstrates that coexistence, confluence and mutual reinforcement between the two perspectives in the school environment is possible.